Constitutively nuclear FOXO3a localization predicts poor survival and promotes Akt phosphorylation in breast cancer. - Jie Chen (Public Library of Science (PLoS), 2010)
Background The PI3K-Akt signal pathway plays a key role in tumorigenesis and the development of drug-resistance. Cytotoxic chemotherapy resistance is linked to limited therapeutic options and poor prognosis. Methodology/principal findings Examination of FOXO3a and phosphorylated-Akt (P-Akt) expression in breast cancer tissue microarrays showed nuclear FOXO3a was associated with lymph node positivity (p = 0.052), poor prognosis (p = 0.014), and P-Akt expression in invasive ductal carcinoma. Using tamoxifen and doxorubicin-sensitive and -resistant breast cancer cell lines as models, we found that doxorubicin- but not tamoxifen-resistance is associated with nuclear accumulation of FOXO3a, consistent with the finding that sustained nuclear FOXO3a is associated with poor prognosis. We also established that doxorubicin treatment induces proliferation arrest and FOXO3a nuclear relocation in sensitive breast cancer cells. Induction of FOXO3a activity in doxorubicin-sensitive MCF-7 cells was sufficient to promote Akt phosphorylation and arrest cell proliferation. Conversely, knockdown of endogenous FOXO3a expression reduced PI3K/Akt activity. Using MDA-MB-231 cells, in which FOXO3a activity can be induced by 4-hydroxytamoxifen, we showed that FOXO3a induction up-regulates PI3K-Akt activity and enhanced doxorubicin resistance. However FOXO3a induction has little effect on cell proliferation, indicating that FOXO3a or its downstream activity is deregulated in the cytotoxic drug resistant breast cancer cells. Thus, our results suggest that sustained FOXO3a activation can enhance hyperactivation of the PI3K/Akt pathway. Conclusions/significance Together these data suggest that lymph node metastasis and poor survival in invasive ductal breast carcinoma are linked to an uncoupling of the Akt-FOXO3a signaling axis. In these breast cancers activated Akt fails to inactivate and re-localize FOXO3a to the cytoplasm, and nuclear-targeted FOXO3a does not induce cell death or cell cycle arrest. As such, sustained nuclear FOXO3a expression in breast cancer may culminate in cancer progression and the development of an aggressive phenotype similar to that observed in cytotoxic chemotherapy resistant breast cancer cell models.